Usability Assessment of a Cable-Driven Exoskeletal Robot for Hand Rehabilitation - Tsai, Yu-Lin; Huang, Jian-Jia; Pu, Shu-Wei; Chen, Hsiang-Peng; Hsu, Shao-Chih; Chang, Jen-Yuan; Pei, Yu-Cheng (Frontiers in Neurorobotics, 2019)
Study design: case series. Background: Robot-assisted rehabilitation mediated by exoskeletal devices is a popular topic of research. The biggest difficulty in the development of rehabilitation robots is the consideration of the clinical needs. This study investigated the usability of a novel cable-driven exoskeletal robot specifically designed for hand rehabilitation. Methods: The study consists of three steps, including prototype development, spasticity observation, and usability evaluation. First, we developed the prototype robot DexoHand to manipulate the patient’s fingers based on the clinical needs and the cable-driven concept established in our previous work. Second, we applied DexoHand to patients with different levels of spasticity. Finally, we obtained the system usability scale (SUS) and assessed its usability. Results: Two healthy subjects were recruited in the pre-test, and eighteen patients with stroke and four healthy subjects were recruited in the formal test for usability. The total SUS score obtained from the patients and healthy subjects was 94.77 ± 2.98 (n = 22), indicating an excellent level of usability. The satisfaction score was 4.74 ± 0.29 (n = 22), revealing high satisfaction with DexoHand. The tension profile measured by the cables showed the instantaneous force used to manipulate fingers among different muscle tone groups. Conclusions: DexoHand meets the clinical needs with excellent usability, satisfaction, and reliable tension force monitoring, yielding a feasible platform for robot-assisted hand rehabilitation. Keywords: Upper distal limb rehabilitation, stroke, rehabilitation device, usability, exoskeleton.